The 2016 Austrian Presidential Election: A Tale of Three Divides. Issue 3 (26th May 2016) - Gavenda, Mario; Umit, Resul
ABSTRACT: The 2016 Austrian presidential election was remarkably different than the previous ones in the history of the country characterized by its stable political system. Not only did it open the role of president in Austria to debate, but it also sidelined the two political parties that had dominated Austrian politics since World War II. Alexander Van der Bellen won the election with one of the closest margins in recent history. This article argues that the election divided the country in more than one way. Besides the near 50–50 divide between the candidates, the results show that it generated important dynamics in territorial politics as well, notably in the states and cities of Austria. These results point towards a party system transformation in Austrian politics.